Coretax Platform Quality And Corporate Taxpayer Satisfaction:: Interface, System, Information-Feature, Service-Security Effects, and Digital Literacy as A Boundary Condition - Muhammad Mukhram; Wulan Ayuandiani (Vifada Management and Social Sciences, 2026)
Purpose: This study examines the effects of interface and usability quality, system reliability and accessibility, information and feature quality, and service and security assurance on corporate taxpayer satisfaction with Coretax as an integrated digital tax administration platform. It also examines digital literacy as a boundary condition in the relationship between interface quality and satisfaction. Research Method: A quantitative survey was conducted involving 50 corporate taxpayers who had used Coretax. Data were collected using 15 reflective indicators measured on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results and Discussion: All four platform quality dimensions have positive and significant effects on taxpayer satisfaction. Information and feature quality is the strongest predictor, followed by service and security assurance, system reliability and accessibility, and interface and usability quality. Digital literacy also plays an important role in strengthening users’ ability to utilize interface quality effectively. Implications: Tax authorities should prioritize feature integration, system stability, service and security assurance, interface usability, and taxpayer digital capability to support sustainable digital tax administration. Originality: This study provides an integrated assessment of Coretax quality from the corporate taxpayer perspective and incorporates digital literacy as a theoretically relevant boundary condition in explaining taxpayer satisfaction.